Pengaruh Jenis Pengeringan Terhadap Uji Organoleptik Penyedap Rasa Alami Berbahan Keong Sawah - Nisrina, Balqis Fatin; Aprialdi, Muhammad Agung (Jurnal Ilmiah Pangan Halal, 2023)
Flavoring is divided into natural and artificial. Natural flavoring is an alternative that is safer to consume than artificial flavoring which has a negative effect on health. One type of natural flavoring is broth. In this research, an experiment was carried out to make natural flavoring or broth made from rice field snails. The purpose of this research is to use rice field snails to make natural flavoring with high protein content. The method used is experimental. The manufacturing process is rice field snails cleaned and boiled with lime to remove the fishy smell, dried using two methods, namely drying in the sun (T72) and roasting (T57). The broth product was then tested on 30 panelists after which the data was analyzed using the Mann-test. Whitney on texture, color, taste and aroma as well as organoleptik tests, Whitney on texture, color, taste and aroma as well as organoleptik tests. 0.389 (no difference). Based on the results of organoleptik tests on T72 and T52 products, namely in terms of color 7 = like), aroma (3.5 and 3.6 = like), texture (3.9 and 3.7 = like), taste (3.5 and 3.7 = like) The results obtained in this study are that the rice field snails can be accepted by the community to be used as ingredients for making natural flavoring which is safe for consumption and contains protein.